Imaging Evaluation of Medial and Lateral Elbow Pain: Acute and Chronic Tendon Injuries of the Humeral Epicondyles - Daniels, Steven P.; De Tolla, Jadie E.; Azad, Ali; Fritz, Jan (Seminars in Musculoskeletal Radiology, 2021)
Medial and lateral elbow pain are often due to degenerative tendinosis and less commonly due to trauma. The involved structures include the flexor-pronator tendon origin in medial-sided pain and the extensor tendon origin in lateral-sided pain. Multimodality imaging is often obtained to verify the clinically suspected diagnosis, evaluate the extent of injury, and guide treatment decisions. Image-guided procedures can provide symptom relief to support physical therapy and also induce tendon healing. Surgical debridement and repair are typically performed in refractory cases, resulting in good to excellent outcomes in most cases. In this article, we review and illustrate pertinent anatomical structures of the distal humerus, emphasizing the structure and contributions of the flexor-pronator and extensor tendon origins in acute and chronic tendon abnormalities. We also discuss approaches to image-guided treatment and surgical management of medial and lateral epicondylitis.
Keywords: elbow; magnetic resonance imaging; ultrasonography; flexor-pronator tendon; common extensor tendon